Unbranding Confrontation as Only a Trial Right - Sanders, Shaakirrah R. (2014)
This Article challenges the oft-cited but unpersuasive rule that the Sixth Amendment Confrontation Clause only applies at the trial stage of a “criminal prosecution.” I examine the most likely interpretation of the term “criminal prosecution” at the time of the Founding and conclude that the term would have included felony sentencing. I explore the Counsel Clause’s early rejection of the “trial-right-only” rule and the recent erosion of the “trial-right-only” rule with regard to the Jury Trial Clause in Alleyne v. United States. I advocate for eliminating the trial-right-only theory of the Confrontation Clause to allow cross-examination of testimonial statements that are material to punishment and where cross-examination assists in assessing truth and veracity. In such cases, I advocate a practical application of the fundamental right to confront witnesses during felony sentencing. Ultimately, I propose a uniform application of the Sixth Amendment’s structurally identical Counsel, Jury Trial, and Confrontation Clauses at felony sentencing